Synthetic, photophysical and biological studies into new tools for investigating bile acid disposition and toxicity - Májer, Ferenc (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2013)
The overall objective of this thesis was to use synthetic chemistry to provide tools to understand problems in bile acid research including their disposition and mechanism of toxicity. Fluorescent reporter groups are very widely used for probing problems of biochemical distribution and mechanism especially in the bile acid field. This area is reviewed here, structured by fluorescent derivatizing agent.Our group has a particular interest in how bile acids induce cell death (this is particularly important in the case of deoxycholic acid (DCA), lithocholic acid (LCA) and chenodeoxycholic acid (CDCA)). There are many questions about the biochemistry, physiology and pharmacology of these bile acids connected in some way to their disposition and especially cellular localization that suitable fluorescent reporters could help answer. To answer questions we designed and synthesized ursodeoxycholic acid (UDCA) and DCA analogues with a reporter group (dansyl or 7-nitrobenzofurazan 2-oxa-l,3-diazole (NBD)) incorporated in the A ring and we also synthesized the appropriate control substances.
Keywords: Pharmaceutical Chemistry, Ph.D.; Ph.D. Trinity College Dublin